PEMBINAAN AKUNTANSI UMKM BAGI USAHA MIKRO KECIL MENENGAH (UMKM) UNTUK MENINGKATKAN KINERJA KEUANGAN DIKELURAHAN SEILEKOP - Efriyenti, Dian (EDUTECH CONSULTANT, 2018)
KUBE UKM registered at Sei Lekop Village is a small and medium-sized business that manufactures and markets fish crackers, SMEs in agriculture (farming), in the field of fisheries, snacks, Mandiri Bank, mega snacks and cookies. The problems currently faced by MSMEs are financial reports compiled each period not yet with financial accounting standards of entities without public accountability, MSME actors find it difficult if they have to use accounting in their business activities, inability and unwillingness to use accounting, and many MSME actors feel that activities the business was running normally but actually the MSMEs had not progressed. The presentation of accounting guidance that is based on the actual conditions in the MSME business and the use of the right approach will make SMEs understand accounting quickly and easily. The method used in the training that will be given to small and medium enterprises in Sei Lekop Village is the survey method, lecture method, discussion method and training method. Sustainability from the results of coaching activities is expected that SMEs are able to understand the recording and objectives in the financial statement notes, SMEs are able to analyze and make financial reports independently in accordance with the accounting cycle of each period based on SAK-ETAP. The results of the SME service felt that there was still a need to adjust the preparation of financial statements with the entity's financial accounting standards without public accountability, to improve the financial performance of MSMEs running smoothly.